Miniaturised ultra‐wideband circular polarised koch fractal crossed dipole array - Won Min Choi; Taeyong Jeong; Dong Hwan Lee; Jun Hee Kim; Dong Geun Lee; Keum Cheol Hwang (IET Microwaves, Antennas & Propagation)
Abstract Ultra‐wideband (UWB) systems utilise a broad frequency spectrum to achieve high data transmission rates and enhanced precision, creating a demand for specialised UWB antennas. Circularly Polarised (CP) antennas are considered essential for maintaining robust performance under varied environmental conditions. Among them, the crossed dipole is effective for UWB CP applications, but its relatively large size could limit its use in various systems. A miniaturised crossed dipole design employing the Koch fractal structure is proposed and the measurement results are presented. The prototype antenna achieved an effective bandwidth covering 88% of the frequency range from 1.4 to 3.6 GHz. Additionally, a 4 × 4 array using this design was tested in the same frequency band, demonstrating beam‐steering capabilities up to 30°. The proposed antenna has demonstrated effective deployment in diverse communication systems and phased array applications within ultra‐wideband (UWB) CP environments.